2022
DOI: 10.3390/foods11162416
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Residual Herbicide Atrazine in Agri-Food and Washing Water

Abstract: Atrazine, an herbicide used to control grassy and broadleaf weed, has become an essential part of agricultural crop protection tools. It is widely sprayed on corn, sorghum and sugar cane, with the attendant problems of its residues in agri-food and washing water. If ingested into humans, this residual atrazine can cause reproductive harm, developmental toxicity and carcinogenicity. It is therefore important to find clean and economical degradation processes for atrazine. In recent years, many physical, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 172 publications
0
8
0
Order By: Relevance
“…This means that the primary substance has been completely degraded into products with lower m/z. According to the products identified in (Table 3 ) and the reports of other researchers 11 , 31 , 37 , 54 58 , the proposed mechanism in the study for the degradation of atrazine is reported in (Fig. 14 ).…”
Section: Resultsmentioning
confidence: 95%
“…This means that the primary substance has been completely degraded into products with lower m/z. According to the products identified in (Table 3 ) and the reports of other researchers 11 , 31 , 37 , 54 58 , the proposed mechanism in the study for the degradation of atrazine is reported in (Fig. 14 ).…”
Section: Resultsmentioning
confidence: 95%
“…The toxicity ranking of atrazine and its metabolites is ATZ > DEA > DIA > AM > DDA > HA. 3 For high frequency ultrasound treatment, after 2 h, the atrazine degradation rate was unfavorable at only 47%, and adding ferrous ions doubled the degradation rate to 87%, but the disadvantages still exist with the presence of toxic main metabolites and a high energy consumption. For Fenton oxidation, although it reached the highest atrazine degradation rate of 95%, it produced toxic main metabolite AM.…”
Section: Resultsmentioning
confidence: 99%
“…12 The degradation of residual atrazine is thus becoming an urgent issue for environmental protection, especially for water security which is listed as a priority by the "European Green Deal" proposed by the European Commission. The degradation of chemically stable atrazine is challenging, and common water treatment technologies are limited by trace organic concentrations 13 and strict fouling control, 14 so there have been increasing efforts to develop efficient advanced oxidation processes, 3 such as Fenton/Fenton-like oxidation, [15][16][17] ultrasound [18][19][20] and so on. Among them, high voltage electrical discharge (HVED) has attracted more attention because of its advantages, high degradation efficiency and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those practices depend on the regulations of the country. Over the last decade, in the EU, the list of approved herbicides, such as Atrazine, Asulam-based herbicides and glyphosate-based products, has decreased, triggering some difficulties in weed control [27][28][29]. The current general trend is to reduce the use of herbicides by adopting new weed control strategies, including innovative cultural and biological technology [25,30].…”
Section: Figurementioning
confidence: 99%